Pengembangan Media Pembelajaran Menggunakan Eksperimen Pencampuran Zat Untuk Meningkatkan Kecerdasan Pada Siswa SMP - Elviana Elviana; Adinda Khairuni (Milenial: Journal for Teachers and Learning, 2021)
In the teaching and learning process using the experimental method, students are given experience to experience for yourself about an object, analyze, prove, and draw conclusions about a state object. With using experimental methods in learning, students are expected to solve problems related to experiments conducted by students and then discussed in order to obtain a solution based on experience students, supported by data sources or facts that exist in reality. By therefore, design a detailed research plan. the scientific method you have to do: formulate the problem, find out hypotheses, establish research variables, establish work procedures, collect data, process and analyze data, make conclusions, discuss research results.